Acoustic emission of the Briggs-Rauscher oscillatory reaction: effect of stirring - RZESZOTARSKA, J.; REJMUND, F. R. (Archives of Acoustics, 2000)
The acoustic emission method has been applied to the investigation of the dependence of the oxygen release in the Briggs-Rauscher oscillatory reaction on the rate of stirring. The oxygen distribution does not increase toward a limiting value but achieves a maximum and decreases afterwards. There exists a low stirring rate at which the release of oxygen from the solution proceeds in the form of "fountains". This can be observed before the disappearance of the iodine oscillations. The results obtained by the acoustic emission method can be useful in the description of the unknown mechanism of the Briggs-Rauscher reaction.